Spectrum of Congenital Malformations - At A Tertiary Hospital - Kumar Murugesan, Dr. Dinesh (Journal of Neonatal Surgery, 2025)
Congenital anomalies have emerged as one of the leading cause of perinatal mortality and morbidity all over the world. Congenital malformations representsdysmorphogenesisoccuringin early fetal life. We are in need of systematic data on the magnitude of congenital anomalies, their prevalence, and their impact on neonatal health. The aim of this study was to determine the prevalence of lethal and non lethalcongenital anomalies observed during 2024-2025 . The study was conducted in the Department of Radiology, Sri Lalithambigai medical college and hospital, a tertiary care hospital in Chennai, from March 2024 – February 2025 .